MEMBANGUN SINERGI BANK-BUMN-UKM: PROBLEM DAN SOLUSI - Isgiyarta, Jaka (JURNAL BISNIS STRATEGI, 2005)
Role of micro, middle business a.nd Cooperation firm in national Economics is significant, specially in Indonesia Economics crisis. Government regulation by  KEPMEN BUMN NO 236/MBU/2003  has strong effect in empowerment for micro, middle business and Cooperation firm, even Its focus in funding resources. Based on empiricial analysis, the weakness of micro, middle businees and Cooperation firm not only in funding, but in production, marketing, management too. It is better make value chain relationship BUMN - micro, midle business and Cooperation firm   to increase their capability. In the others,  focus on  tunding resources, It is necessary to create understanding relationship between bank and micro, midle businees and Cooperation firm.